Basil cell carcinoma: an immunohistochemical assessment of P53, BCL-2 and CD138 in low and high-risk histological subtypes - De Stadler, Janet (Department of Clinical Laboratory Sciences, 2024)
Basal cell carcinoma (BCC) is the leading cancer in males and the second commonest cancer in females in South Africa. The cost to the health sector is expected to rise given the increasing global incidence rates, particularly of aggressive BCCs. Improved understanding of BCC is paramount to enhance early detection and screening which could potentially offset these rising costs. Specific histological patterns of BCC have been defined as high-risk for recurrence by the World Health Organisation. The different BCC subtypes are not simply architectural patterns but may represent differences in aetiopathogenesis and protein expression, and impact future targeted therapies. Upregulation of the Hedgehog pathway and TP53 inactivation are the two most common events in the development of BCCs. High-risk BCC patterns have been observed to show increased expression of tumoural p53 and decreased expression of BCL-2 and CD138 compared with low-risk patterns. In addition, peritumoural expression of CD138 has been noted to increase in the stroma of high-risk BCCs. These observations have largely been made by light microscopy rather than with digital analysis.